Effects of motivation and tool features on online photo‐sharing behavior. Issue 1 (18th October 2019) - Cho, Hyerim; Smith, Josh; Lee, Jin Ha
ABSTRACT: Sharing photos online has become one of the most popular information sharing behaviors in recent years. Due to the plethora of online photo‐sharing websites, applications, and other tools available, we share visual information easily, and quickly. In order to improve our current understanding of photo‐sharing behaviors and identify the exhaustive list of online photo‐sharing motivations, we analyzed 4, 555 photos shared online. Seventeen interviewers interviewed 92 participants overall. Twenty photo‐sharing motivations were identified in this study, including To share memory, To disseminate information, For amusement (humor, fun), To show off, and To appreciate beauty/cuteness.